Critical Analysis of Nursing Practices in Chronic Disease Management and Patient Advocacy - Alshammari, Seham Nawaf Hazza; Alziany, Munifa Maleh Mohsen; Alreshidi, Maliha Mutarid Awadh; Alrashidi, Sharifah Maleh Mohsen; Reshidi, Sarah Saud Eid; hail, Abdulelah Khalid Abdulaziz Aldayud; Alshammeri, Amal Saud; alshammari, Entsar Saud Awnan; Alharbi, Sultan Kayid; Alheeh, Nourah Hassan Dhaim (Journal of Ecohumanism, 2024)
The major non-communicable diseases include diabetes, hypertension, and cardiovascular diseases, which are some of the biggest health concerns worldwide. Chronic illness management is an important aspect of care in nursing professionals, as they develop relationships with their clients and provide critical medical care, counseling, and education. This paper is a critical discussion of the current nursing practice in managing chronic diseases, pointing out the significance of the nurse in enhancing patient success. It examines how nurses communicate with or interact with patients, interprofessional relationships, and nursing advocacy. The review also covers the elements of evidence-based practice and discusses the issues and prospects for chronic illness management about patient-centeredness.